(untitled) (Journal of Management and Educational Sciences, 2024)
In this research, web-supported teaching, web-based teaching and traditional teaching methods are compared in terms of their effects on student success. The research design used in the study is a 3x2 split-plot (mixed) design. According to the research results; It was determined that there was an increase in the success of the groups in which traditional, web-based and web-assisted teaching methods were applied, according to the tests applied before and after the experiment. It was determined that there was no difference between the pre-test results in all three groups where different teaching methods were applied. It was determined that there was a difference between the post-test results of the three different groups, to which different teaching methods were applied, after the experiment. In other words, there is a difference in post-test applications between groups in terms of student success. It is seen that the third group, for which the web-based teaching method was applied for the Spreadsheets (MS Excel) module, was the most successful group, the second group, for which the web-based teaching method was applied, was the second successful group, and the first group, for which the traditional teaching method was applied, was the least successful group. In the Information and Communication (MS Outlook) module, it was determined that there was an increase in the success of the groups in which traditional, web-based and web-assisted teaching methods were applied, according to the tests applied before and after the experiment. It was determined that there was no difference between the pre-test results in all three groups where different teaching methods were applied. In other words, there is no difference in terms of student achievement between groups. It was determined that there was no difference between the post-test results of the groups to which the traditional and web-based teaching method was applied in terms of student success among the groups to which different teaching methods were applied, but there was a difference between the post-test results of the groups to which the web-assisted teaching method and both traditional and web-based teaching methods were applied. For the Information and Communication (MS Outlook) module, it is seen that the third group, for which the web-based teaching method was applied, was the most successful group, and there was no difference between the success of the second group, for which the web-based teaching method was applied, and the first group, for which the traditional teaching method was applied.